2017
DOI: 10.1038/s41598-017-06780-1
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-induced osteogenic potential of human amniotic fluid stem cells via CD73-generated adenosine production

Abstract: The human amniotic fluid stem cell (hAFSC) population consists of two morphologically distinct subtypes, spindle-shaped and round-shaped cells (SS-hAFSCs and RS-hAFSCs). Whilst SS-hAFSCs are routinely expanded in mesenchymal-type (MT) conditions, we previously showed that they acquire broader differentiation potential when cultured under embryonic-type (ET) conditions. However, the effects of culture conditions on RS-hAFSCs have not been determined. Here, we show that culturing RS-hAFSCs under ET conditions co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
5
4
0
Order By: Relevance
“…It is in accordance with recent studies on human amniotic fluid-derived MSCs published by Hau et al (2017). The authors demonstrated that the transforming growth factor beta (TGFβ)-induced activation of CD73, and the following increase in the generation of extracellular Ado triggered faster proliferation and enhanced the efficiency of osteogenic differentiation of the cultured cells.…”
Section: Osteogenic Differentiationsupporting
confidence: 90%
See 1 more Smart Citation
“…It is in accordance with recent studies on human amniotic fluid-derived MSCs published by Hau et al (2017). The authors demonstrated that the transforming growth factor beta (TGFβ)-induced activation of CD73, and the following increase in the generation of extracellular Ado triggered faster proliferation and enhanced the efficiency of osteogenic differentiation of the cultured cells.…”
Section: Osteogenic Differentiationsupporting
confidence: 90%
“…It is in accordance with recent studies on human amniotic fluid-derived MSCs published byHau et al (2017). The authors demonstrated that the transforming growth factor beta (TGFβ)-induced activation of CD73, and the following increase in the generation of extracellular Ado triggered faster proliferation and enhanced the efficiency of osteogenic differentiation of the cultured cells.The number of potential clinical applications of adult MSCs in bone repair is rapidly growing, particularly in diseases where the bone destruction rate exceeds the bone formation one, for example, osteoporosis, rheumatoid arthritis, and fracture mal-union (Noronha-Matos & Correia-de-Sá, 2016).…”
supporting
confidence: 91%
“…Conversely, MC3T3‐E1 cells overexpressing CD73 exhibit increased amounts of osteocalcin and bone sialoprotein 2, higher ALP activity, and extensive areas of calcified bone nodules when compared to controls 97 . These findings are in accordance with recent studies on human amniotic fluid‐derived MSCs treated with transforming growth factor‐beta (TGFβ), which induces activation of the CD73 enzyme, increases the production of extracellular Ado, and triggers a faster proliferation with enhanced osteogenic differentiation 163 . Likewise, the absence of Ent1 in knockout mice, which results in inhibition of Ado reuptake, leads to increased ectopic calcification of spinal tissues 120 .…”
Section: Adenosinergic Signaling In Mesodermal Differentiationsupporting
confidence: 88%
“…Moreover, also high expression levels of e-5'NT were evidenced in human osteoprogenitor cell lines as well as in human BMSCs and mesenchymal progenitor cells in human trabecular bone [161][162][163]. The activity of this enzyme contributes to the osteogenic activity induced by transforming growth factor ß (TGFß) in human amniotic fluid stem cells [164]. The high expression/function of e-5'NT is coupled to a reduced expression of adenosine deaminase, the enzyme converting adenosine into inosine, thus assuring appropriate levels and prolonged activity of the extracellular adenosine in MSCs [162].…”
Section: Expression and Role Of Purine Ecto-enzymes In Msc Biological Functionsmentioning
confidence: 99%